Trend Analysis Of Net Profit at Sharia Bank - LUBIS, M ZAKY MUBARAK (Universitas Siliwangi, 2024)
Introduction to The Problem: During the Covid-19 period, the financial world experienced obstacles in achieving net profit, including Islamic banks. How is the current net profit trend of Islamic banks seen from various trend analysis methods.Purpose/Objective Study: To determine the trend of Bank Muamalat's net profit using linear, quadratic and exponential trend methods.Design/Methodology/Approach: This paper uses a descriptive method with a quantitative approach.Findings: The research findings show that there is a downward trend in net Profit from Bank Muamalat in all three trend analysis methods and the quadratic trend method is the most accurate method with the largest R Square value compared to the linear trend and exponential trend.Paper Type: Research Article